2021
DOI: 10.3389/fgene.2021.648800
|View full text |Cite
|
Sign up to set email alerts
|

Whole Transcriptome Data Analysis Reveals Prognostic Signature Genes for Overall Survival Prediction in Diffuse Large B Cell Lymphoma

Abstract: BackgroundWith the improvement of clinical treatment outcomes in diffuse large B cell lymphoma (DLBCL), the high rate of relapse in DLBCL patients is still an established barrier, as the therapeutic strategy selection based on potential targets remains unsatisfactory. Therefore, there is an urgent need in further exploration of prognostic biomarkers so as to improve the prognosis of DLBCL.MethodsThe univariable and multivariable Cox regression models were employed to screen out gene signatures for DLBCL overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…S7 ). Furthermore, the comparison of ROC curves with existing gene expression-based classifiers [ 27 , 28 , 41 ] demonstrated that our 24-gene risk score had the best performance in predicting two-year outcomes (Fig. S8 ).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…S7 ). Furthermore, the comparison of ROC curves with existing gene expression-based classifiers [ 27 , 28 , 41 ] demonstrated that our 24-gene risk score had the best performance in predicting two-year outcomes (Fig. S8 ).…”
Section: Resultsmentioning
confidence: 92%
“…However, the focus has been largely on OS, rather than specifically addressing features associated with early disease progression. Some studies have developed risk models by incorporating OS data from patients treated with CHOP and R-CHOP [ 27 , 28 ], whereas some risk signatures were developed without validation cohorts or based on limited sample sizes [ 26 , 29 ]. Moreover, none of these risk models/signatures attempted to integrate both genetic and transcriptomic data in their evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is worth noting that ACSM3 has demonstrated tumor-immunosuppressive properties in high-grade serous ovarian cancer, and ENPP7 activity has been relatively low in diseases with an increased risk of liver tumorigenesis [ 39 , 40 ]. Among the 16 genes, only FASN and CYP27A1 have been previously reported in DLBCL [ 15 , 16 , 41 , 42 ]. Nevertheless, the biological processes in which these 16 genes are involved have been well-established in DLBCL, including biosynthesis, transport, and beta-oxidation of fatty acids, as well as acyl-CoA flux within cells and lipid metabolism [ 16 , 17 , 43 45 ].…”
Section: Discussionmentioning
confidence: 99%